Innovative work behaviour in employed homemakers: The role of work-family balance and resilience - Puspa Damayanti, Dhestria Wira; Kurniawan, Jimmy Ellya (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Global competition requires many employees to develop innovative work behavior, including those with double roles. The role demands of employees and homemakers put them under heavy pressure, requiring work-family balance and coherence to improve their innovative work behavior. This study aims to test the effects of work-family balance and resilience on innovative work behavior in employed homemakers. The study adopted a quantitative approach by spreading an online questionnaire to 103 already-married corporate employees. The regression analysis results show a significant influence between work-family balance and resilience in innovative work behavior, with a total effective contribution of 62.1%. However, based on the results of the stepwise test, the work-family balance only contributed 4.1%, while occupational resilience contributed to 58% of innovative work behavior.